DYSLIPIDEMIA CHANGES EXERCISE ENERGY EXPENDITURE IN MICE TRANSGENIC FOR HUMAN APOCIII - Nilton Rodrigues Teixeira Junior; Diogo Rodrigues Jimenes; Cristiany Schultz; Jairo Augusto Berti (Arquivos do Mudi, 2023)
Hypertriglyceridemia is a predisposing factor for several metabolic diseases in the worldtoday. Their cause is multifactorial, several factors are directly linked to the modification ofplasma lipid metabolism, among them are genetics and exercise. The genic overexpression ofapoCIII makes the animal hypertriglyceridemic and high levels of blood cholesterol, enablingfurther studies to be done on its metabolic profile. This study investigates how apoCIIIoverexpression and exercise modify the metabolism of genetically modified mice, especiallytheir energy expenditure. We used 15-month-old male C57Bl/6 mice, subdivided into 4groups: 2 NTG groups (non-transgenic mice that were submitted to training and theircontrols) and 2 CIII groups (transgenic Mice with basal triglyceridemia above 300mg/dL thatwere submitted to training and their controls). The exercised groups underwent for 8 weeks amoderate intensity training for 40 minutes 3 times a week. All animals were submitted to astress test to evaluate performance and energy expenditure. The trained animals had higherenergy expenditure during all stages of the test (p<0.01) and the area under curve of the EEshowed that the trained animals had higher caloric consumption (p<0.001), while the animalCIII sed had a much higher energy expenditure than its control NTG sed (p<0.001). Weconclude that dyslipidemia makes the CIII animal less fit for exercise, and trained animalshave lower energy expenditure independent of dyslipidemia and produced more work.